Thermal design of heat exchangers a numerical approach - direct sizing and stepwise rating - Smith, Eric M. (John Wiley Chichester, 1997)
This book is unique in adopting a numerical approach to the thermal design of heat exchangers. The computation of mean temperature difference, with accommodation of longitudinal conduction effects, makes full optimisation of the exchanger core possible. Sets of three partial differential equations for both contra-flow and cross-flow are established, and form the bases from which a range of methods of direct-sizing and stepwise rating may proceed. Optimisation of an exchanger for steady-state operation is achieved by an approach which allows maximum utilisation of the allowable pressure losses. Transient methods are covered, including the Method of Characteristics, and the Single-Blow method of testing is treated. Numerous aspects of low and high temperature design are discussed, and extensive references to the literature are provided. Schematic algorithms are listed to allow students and practitioners to construct their own solutions, and spline-fitting of data is discussed.
Includes index
Keywords: Heat exchangers -- Design and construction